2004
DOI: 10.1161/01.cir.0000140667.37070.07
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Promote Cardiac Myocyte Survival and Spatial Reorganization

Abstract: Background-Endothelial-cardiac myocyte (CM) interactions play a key role in regulating cardiac function, but the role of these interactions in CM survival is unknown. This study tested the hypothesis that endothelial cells (ECs) promote CM survival and enhance spatial organization in a 3-dimensional configuration. Methods and Results-Microvascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
260
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(281 citation statements)
references
References 41 publications
18
260
0
3
Order By: Relevance
“…These data are consistent with the fact that we have recently demonstrated that the presence of endothelial cells improves survival and organization of cardiomyocytes in vitro. 13 The data in the present study suggest that endothelial cell presence within the peptide microenvironments may be important in cell survival and recruitment. Furthermore, we saw development of functional ␣-smooth muscle actin- positive vessels within the myocardium, including some with red blood cells within, suggesting that angiogenesis also occurs within the microenvironment with a specific time course and that new vessels are capable of connection to the host vasculature.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These data are consistent with the fact that we have recently demonstrated that the presence of endothelial cells improves survival and organization of cardiomyocytes in vitro. 13 The data in the present study suggest that endothelial cell presence within the peptide microenvironments may be important in cell survival and recruitment. Furthermore, we saw development of functional ␣-smooth muscle actin- positive vessels within the myocardium, including some with red blood cells within, suggesting that angiogenesis also occurs within the microenvironment with a specific time course and that new vessels are capable of connection to the host vasculature.…”
Section: Discussionmentioning
confidence: 50%
“…13 To determine whether microenvironments can be established with injected peptides in vivo, the LV free wall of adult male C57BL6 mice was injected with 1% RAD16-II immediately after suspension of peptides at pHϭ7.0 and osmolarity of 295 mOsm. The hearts were later excised, fixed in 4% (wt/vol) paraformaldehyde, and embedded in paraffin.…”
Section: Detection Of Injected Peptide Gel and Cell Infiltrationmentioning
confidence: 99%
“…RADA16 spontaneously assembles in the presence of monovalent salt or under physiological conditions as a result of both the ionic side chain interactions and the conventional b-sheet propensity of the backbone, ultimately forming a macroscopic hydrogel known to facilitate cell culture. 14,[16][17][18] Cell attachment and neurite outgrowth were enhanced when neural cells were cultured on this hydrogel. Moreover, cells may be embedded in RADA16 peptide hydrogels, providing a 3-D environment for the cells to grow.…”
Section: Introductionmentioning
confidence: 98%
“…O implante de células-tronco em estruturas biodegradáveis demonstrou ser um método plausível e associado a resultados positivos in vitro 38 . Alternativas envolvendo a combinação de cardiomioplastia celular com terapia genética também vêm sendo testadas com sucesso em modelos experimentais in vivo 39 .…”
Section: Perspectivas Futurasunclassified